Elemental Decomposition and Multicriteria Method for Valuing Transportation Infrastructure. Issue 1 (January 2014) - Dojutrek, Michelle S.; Volovski, Matthew; Labi, Samuel
Traditional valuation methods implicitly consider assets as monolithic entities. As such, the initial costs, characteristics, and behavior of individual asset elements are not adequately accounted for in the valuation. Also criteria, including the asset service life and condition, that reflect the user and agency perspectives of asset value, respectively, need to be considered. A new valuation methodology, the elemental decomposition and multi criteria (EDMC) method, was developed to address those limitations. The proposed method viewed an asset not as a monolithic structure but in relation to its individual elements and recognized that each element deteriorated at a different rate, so the valuation of the asset elements was carried out separately. Individual element values were summed to yield the asset's total value. EDMC also introduced the concept of attribute ratios to tie in the criteria, such as condition and remaining service life. The traditional asset valuation approaches were described, and then the way the EDMC method could be applied at project and network levels was demonstrated. The case study showed that total values of major highway assets in Indiana as of 2012 were pavements, 48 billion; bridges, 8.05 billion; culverts, 0.22 billion; guardrails, 0.33 billion; under drains, 0.006 billion; road signs, 0.02 billion; and right-of-way, 12.3 billion; the total for all considered assets was 68.93 billion. Normalized by using the entire inventory size (27, 879 lane miles), the values for each asset type per lane mile were determined to be pavements, 1.8 million; bridges, 0.289 million; culverts, 7, 893; guardrails, 11, 728; underdrains, 204; and road signs, 713; the loaded unit value for all considered assets was 2.47 million per lane mile. Monte Carlo simulation was used to show how a probabilistic EDMC method could account for uncertainties in asset cost, condition, and remaining life.